EVALUASI LAHAN FISIK DAN EKONOMI KOMODITAS PERTANIAN UTAMA TRANSMIGRAN DI LAHAN MARJINAL KERING MASAM RANTAU PANDAN SP-4, PROVINSI JAMBI - - Widiatmaka; Wiwin Ambarwulan; Setiardi P. Mulya; Benar Darius Ginting-Soeka; - Bondansari (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2014)
Most of the land used for transmigration resettlement activities outside of Java Island is marginal land that requires highproduction inputs and susceptible to degradation. One of the need to be taken into consideration in the choice of location is land suitability. The objective of this study is to determine the land suitability of agricultural transmigration area with a case study of Transmigration Settlement Unit (UPT) of RantauPandan SP-4, Jambi Province, for cultivation of food crops, vegetables and perennial crops and analyse the level of biophysical and economical feasibility of several commodities. The actual land suitability assessment for the three agricultural commodities indicate the dominance land suitability classes of S3 (marginally suitable) with terrain, nutrient retention and nutrients available become dominant limiting factors. Economic land suitability analysis indicate that the biggest gross margin is rubber, while the smallest is rice. Results of analysis are used to determine the spatial land use recommendations on transmigration location. Results of analysis are not always in line with the transmigration pattern of land allocation. Nonetheless, these results suggested to be applied, for considerations of land conservation as well as farmers' welfare.Keywords: land suitability, automated land evaluation system, land quality, land characteristic